2-Methyl-4-chlorophenoxyacetic acid (MCPA) sorption and desorption as a function of biochar properties and pyrolysis temperature. - Abdullah Niaz; Kurt A Spokas; Bea Gámiz; David Mulla; Khaliq R Arshad; Sarfraz Hussain (PLoS ONE, 2023)
2-Methyl-4-chlorophenoxyacetic acid (MCPA) is a highly mobile herbicide that is frequently detected in global potable water sources. One potential mitigation strategy is the sorption on biochar to limit harm to unidentified targets. However, irreversible sorption could restrict bioefficacy thereby compromising its usefulness as a vital crop herbicide. This research evaluated the effect of pyrolysis temperatures (350, 500 and 800°C) on three feedstocks; poultry manure, rice hulls and wood pellets, particularly to examine effects on the magnitude and reversibility of MCPA sorption. Sorption increased with pyrolysis temperature from 350 to 800°C. Sorption and desorption coefficients were strongly corelated with each other (R2 = 0.99; P < .05). Poultry manure and rice hulls pyrolyzed at 800°C exhibited irreversible sorption while for wood pellets at 800°C desorption was concentration dependent. At higher concentrations some desorption was observed (36% at 50 ppm) but was reduced at lower concentrations (1-3% at < 5 ppm). Desorption decreased with increasing pyrolysis temperature. Sorption data were analyzed with Langmuir, Freundlich, Dubinin-Radushkevich and Temkin isotherm models. Freundlich isotherms were better predictors of MCPA sorption (R2 ranging from 0.78 to 0.99). Poultry manure and rice hulls when pyrolyzed at higher temperatures (500 and 800°C) could be used for remediation efforts (such as spills or water filtration), due to the lack of desorption observed. On the other hand, un-pyrolyzed feedstocks or biochars created at 350°C could perform superior for direct field applications to limit indirect losses including runoff and leaching, since these materials also possess the ability to release MCPA subsequently to potentially allow herbicidal action.